Measuring justice: quantitative accountability and the National Prosecuting Authority in South Africa - Mugler, Johanna (Cambridge studies in law and society, 2019)
From apartheid administrators to lawyers of the people : a history of accountability inside the South African Prosecution Authority (1948-2018) -- Ethnographic research in a multi-local organisation : access, challenges and methods -- "Stats talk" and alternative expressions of accountability : NPA lower court prosecutors at work -- No fear of numbers : reactivity and the political economy of NPA performance measurement -- At the top of the NPA : managing with numbers and numerical reflexivity -- Lies, damned lies and statistics : making sense of misleading or imperfect NPAconviction rates -- Concluding remarks